Mpox (Monkeypox): A Comprehensive Overview - Tank, Rakesh; Tank, Priyanka (Disease and Health: Research Developments Vol. 6, 2025)
Monkeypox is a zoonotic viral disease caused by the Monkeypox virus (MPXV), a member of the Orthopoxvirus genus. Initially identified in 1958 in research monkeys, the first human case was identified in 1970 in the Democratic Republic of Congo (DRC). Monkeypox primarily impacts Central and West African regions but has emerged globally as a public health concern, with outbreaks occurring in non-endemic nations. The disease manifests with influenzae-like symptoms, fever, lymphadenopathy, and a distinctive rash that evolves from macules to papules, vesicles, and pustules. Transmission occurs through close contact with infected individuals, body fluids, respiratory droplets, or contaminated surfaces. Zoonotic transmission originates from interaction with diseased animals, especially rats, considered to be the principal reservoirs. The 2022 multi-country outbreak highlighted the risk of human-to-human transmission in highly populated areas and among susceptible groups, including immunocompromised adults and children. The management of monkeypox is supportive, emphasising symptom alleviation and prevention of subsequent infections. Vaccines, including Modified Vaccinia Ankara-Bavarian Nordic (MVA-BN)) and ACAM2000, are effective against susceptible high-risk populations. Antiviral agents like tecovirimat have also shown promising results in severe cases. Containment strategies emphasize surveillance, public awareness, and vaccination campaigns targeting at-risk groups. The emergence of monkeypox underscores the necessity for improved monitoring of zoonotic diseases and international collaboration in tackling neglected tropical diseases.